2018
DOI: 10.1002/alr.22226
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive exosomal proteomic biosignatures, including cystatin SN, peroxiredoxin‐5, and glycoprotein VI, accurately predict chronic rhinosinusitis with nasal polyps

Abstract: BackgroundExosomes are secreted epithelial‐derived vesicles that contain a conserved protein array representative of their parent cell. Exosomes may be reproducibly and noninvasively purified from nasal mucus. The exosomal proteome can be quantified using SOMAscanTM, a highly multiplexed, aptamer‐based proteomic platform. The purpose of this study was to determine whether chronic rhinosinusitis with nasal polyps (CRSwNP) has a unique predictive exosomal proteomic biosignature.MethodsExosomes were isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 39 publications
1
64
0
Order By: Relevance
“…The SOMAscan assay has been well studied, demonstrating a median limit of detection in the picomolar range and a dynamic range across 7 orders of magnitude of protein concentration, as well as a median intraplate coefficient of variability between 3% and 4%. We have recently demonstrated that the SOMAscan is capable of handling the small sample size of exosomal material from patient mucus collection, with Western blot confirmation . The SOMAscan with 3 controls (included with the kit) and 1 buffer control without protein were run in parallel with the samples.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SOMAscan assay has been well studied, demonstrating a median limit of detection in the picomolar range and a dynamic range across 7 orders of magnitude of protein concentration, as well as a median intraplate coefficient of variability between 3% and 4%. We have recently demonstrated that the SOMAscan is capable of handling the small sample size of exosomal material from patient mucus collection, with Western blot confirmation . The SOMAscan with 3 controls (included with the kit) and 1 buffer control without protein were run in parallel with the samples.…”
Section: Methodsmentioning
confidence: 99%
“…CRSwNP symptomatology is severe, often requiring frequent medical and surgical interventions to lower morbidity . Recent advances in our understanding of perturbations observed in the CRSwNP proteome have brought forth new potential diagnostic and therapeutic targets . These advances have come about through large‐scale efforts to analyze the transcriptome and proteome in health and disease, through direct tissue sampling and “liquid biopsy” of exosomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They further noted that the samples collected via polyurethane foam were stable for at least 1 month at 4°C or colder. Like other focal surface fluid collection techniques, foam sponges can be directed at different anatomic regions of interest, such as the internal nasal valve or ethmoid bulla, among others.…”
Section: Techniques For Collection Of Nasal Secretionsmentioning
confidence: 99%
“…Consequently, exosomes may be used as a biomarker that shows great potential for noninvasive diagnostics and conducting “liquid biopsies.” As exosomes represent only a small fraction of the cell's secretome, exosome isolation techniques allow for further analysis of the exosome independent of other cell contents. Exosomes are isolated from nasal mucus, which is often gathered via focal surface fluid collection techniques, as described earlier (eg, polyvinyl acetate sponge application). Once isolated, exosomal samples may be used to study physiologic and pathophysiologic mechanisms, including sinonasal inflammation or malignancy.…”
Section: Techniques For Nasal Mucus Exosome Concentration and Isolationmentioning
confidence: 99%